NINE‐YEAR FOLLOW‐UP OF SPECIFIC PHOBIA IN A POPULATION SAMPLE OF OLDER PEOPLE. Issue 4 (8th December 2015) - Sigström, Robert; Skoog, Ingmar; Karlsson, Björn; Nilsson, Johan; Östling, Svante
Abstract : Background: Little is known about the long‐term course of specific phobia (SP) in the general population. We examined the prevalence and course of SP and subthreshold fears in an older population followed over 9 years. Method: A psychiatric examination was performed in a population‐based sample of 558 70‐year‐olds, among whom 303 dementia‐free survivors were followed up at both ages 75 and 79. Fears were rated with respect to level of anxiety and social or other consequences. DSM‐IV SP was diagnosed when fears were associated with prominent anxiety and had social or other consequences. All other fears were labeled subthreshold fears. Results: The prevalence of SP declined from 9.9% at age 70 to 4.0% at age 79. The reason was that the prevalence of fears associated with prominent anxiety (mandatory in the diagnosis) decreased whereas the prevalence of fears that gave social or other consequences remained stable. A total of 14.5% of the population had SP at least once during the study. Among these, 11.4% had SP and 65.9% had specific fear at all three examinations. Conclusion: The prevalence of fears associated with prominent anxiety decreased with age, resulting in an overall decline in the prevalence of SP. SP seems to be a fluctuating disorder, and in most cases an exacerbation of chronic subthreshold fears.